Environmental constraints at the edge of a species distribution, the Eurasian badger (Meles meles L.): a biogeographic approach - Virgos, E.; Casanovas, J. G. (JOURNAL OF BIOGEOGRAPHY, 1999)
Aim This paper describes the distribution pattern (occurrence) of badgers (Meles meles L. 1758) in a Mediterranean mountain area of central Spain, in relation to landscape characteristics and climatic data. We test the fit of the badger occurrence pattern to the niche hypothesis predictions. Location We sampled twenty-four survey plots randomly distributed in the mountains of central Spain (Sierra de Guadarrama, Madrid): ten in the north and fourteen in the south slopes. All habitat types and climatic conditions typical of central Spain can be found. Methods The ocurrence of badgers ill the plots were recorded through an exhaustive search of setts and latrines in four different (and evenly spaced) points in each plot. The index of occurrence was made by dividing the number of positive points (badger presence) by the total number of points sampled (four in all plots). Landscape patterns (% type of habitat in each plot) were obtained from detailed maps and climate data from meteorological stations placed in the plot. We analyse the contribution of landscape variables and climate data to explain the differences in badger occurrence through Pearson correlations and fixed one-way ANCOVA with climatic data as fixed factor, vegetation cover as covariates and badger occurrence as response variable. Additionally, we use an one-way ANOVA to check the differences in occurrence between north and south plots with the location of each plot as fixed factor. Results The results indicate that the badger is more abundant in rainy areas of the mountains, and in open landscapes vegetated by ash-tree forests than in closed landscapes vegetated by helm oak forests. In addition, the species is more abundant in the northern plots than in the southern ones. Northern plots were homogeneous areas characterized by their open landscape and wet climate, while southern plots were characterized by their dry climate and closed landscapes. In addition, climate (measured as summer rain) is more determinant than habitat type (holm oak cover) to explain the pattern of badger occurrence. Main conclusions Overall, we consider that the typical Mediterranean landscapes are poor habitats for badgers due to changes in the environmental conditions associated with. concomitant changes in food resources. These data support the niche hypothesis to explain the changes in abundance or occurrence close to the edge of the distribution of species, and in particular, in Palearctic species in the Mediterranean area.
The following values have no corresponding Zotero field: pub-location: P O BOX 88, OSNEY MEAD, OXFORD OX2 0NE, OXON, ENGLAND publisher: BLACKWELL SCIENCE LTD
Keywords: Environmental factors; Mediterranean mountains; meles meles; niche hypothesis; species distributions